Pemanfaatan Model Pembelajaran Project Based Learning Berbantu Geospatial Technology Terhadap Berpikir Kreatif Siswa Kelas XI Fase F di SMA Negeri 1 Batang Kapas - Syahwifa, Khaidilla Indah; Wijayanto, Bayu (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the effect of the project based learning model assisted by geospatial technology on the creative thinking skills of class XI Phase F students at SMA Negeri 1 Batang Kapas. This study is a quasi-experimental design study with a pretest posttest control group design. The population of the subjects of this study were 64 students of class XI Phase F who were divided into two classes. Class XI F/8 as the experimental group and class XI F/10 as the control group with the number of students in each class. The data collection technique in this study used a test in the form of 20 multiple-choice questions and 5 essay questions that had been tested for validity and reliability. Hypothesis testing in this study used the Independent T-Test analysis to test the difference in scores obtained by students in the control class and the experimental class after learning (post-test). The results showed that there was an effect of the project based learning model assisted by geospatial technology on the creative thinking skills of class XI Phase F students at SMA Negeri 1 Batang Kapas